2015
DOI: 10.1038/ncomms9523
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-5p and miR-130a-3p are regulated by IL-4 and IL-13 and control profibrogenic macrophage program

Abstract: Macrophages play a pivotal role in tissue fibrogenesis, which underlies the pathogenesis of many end-stage chronic inflammatory diseases. MicroRNAs are key regulators of immune cell functions, but their roles in macrophage's fibrogenesis have not been characterized. Here we show that IL-4 and IL-13 induce miR-142-5p and downregulate miR-130a-3p in macrophages; these changes sustain the profibrogenic effect of macrophages. In vitro, miR-142-5p mimic prolongs STAT6 phosphorylation by targeting its negative regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
192
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 220 publications
(207 citation statements)
references
References 60 publications
14
192
0
1
Order By: Relevance
“…One possibility is that microRNAs (miRs) play a role in regulating expression of these transcripts. Support for this possibility was recently reported in a study were human monocyte-derived macrophages treated with IL-4/IL-13 displayed increased miR-142-5p and decreased miR-130-3p [13]. In the activation model used in this study, miR-142-5p regulated the phosphorylation of STAT6.…”
Section: Introductionsupporting
confidence: 77%
“…One possibility is that microRNAs (miRs) play a role in regulating expression of these transcripts. Support for this possibility was recently reported in a study were human monocyte-derived macrophages treated with IL-4/IL-13 displayed increased miR-142-5p and decreased miR-130-3p [13]. In the activation model used in this study, miR-142-5p regulated the phosphorylation of STAT6.…”
Section: Introductionsupporting
confidence: 77%
“…Notably, if we focus on in vivo human studies, the majority of dysregulated miRs were identified by evaluating whole-lung explants (55)(56)(57)(58)(59)(60)(61)(62)(63)(64). However, the whole lung has multiple cell types (e.g., epithelium, fibroblast, macrophage) that participated in fibroproliferation, and only a limited number of studies confirm the in vivo cellular compartment with dysregulated miR expression (61)(62)(63)(64)(65)(66)(67). In our study, we specifically procured and evaluated a purified population of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…NR3B1 regulates anti-inflammatory macrophage function by inducing Tnfaip3 transcription and controlling metabolic reprogramming in macrophages. IL-4 and IL-13 have also been shown to induce miR-142-5p and downregulate miR-130a-3p in macrophages, which sustains Stat6 activation and pro-fibrotic gene expression (Su et al, 2015). Finally, N-3 polyunsaturated fatty acids, which exhibit substantial anti-inflammatory in vivo , confer important cardio protective effects by inhibiting macrophage-mediated activation of cardiac fibroblasts.…”
Section: Protective Roles For Anti-inflammatory and Anti-fibrotic Macmentioning
confidence: 99%